Maintaining Welfare: Adaptation Strategies of Coffee Farming Communities in Lumajang, Indonesia, 2014-2023 - Latifatul Izzah; Ismail Ali; I. G. Krisnadi; Suharto Suharto; Andang Subaharianto; Sri Ana Handayani; Eko Crys Endrayadi (Indonesian Historical Studies, 2025)
This article aims to analyze the adaptation strategies of farmers in a village on the slopes of Semeru, specifically in Wono Cepoko Ayu Village, Senduro District, Lumajang Regency, which has long been recognized as a coffee cultivation area, namely Kolesem (Kopi Lereng Semeru; Semeru Slope Coffee). In 2014, farmers preferred to plant Balsa Wood and then returned to planting coffee from 2018 to 2023. Therefore, this article analyzes three main issues, namely, the reasons why farmers easily switched from planting coffee to Balsa Wood in 2014, factors that encouraged them to return to planting coffee during 2018-2023, and the impact of the transition on farmer welfare. This study emphasizes the socio-historical aspect with an economic sociology approach, enhanced with rational theory, and applies historical methods. The results of the study show that the transition to Balsa Wood is driven by its high economic potential, which leads to an increase in farmer welfare, such as land purchases and house renovations. However, a virus outbreak in Balsa Wood forced farmers to return to coffee cultivation and adopt intercropping methods to support their economy. This situation highlights that such adaptation remains essential to support farmer welfare and underlines the importance of flexibility in dealing with economic changes and agricultural challenges.